If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying h = 3(1) + 1 Multiply 3 * 1 h = 3 + 1 Combine like terms: 3 + 1 = 4 h = 4 Solving h = 4 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Simplifying h = 4
| 0.2c+0.08c-3.6c=0 | | 9=9-11x | | 0.3(y+2)=24 | | 10z^2-1440=0 | | 28-2u=5u | | 2x+14=-5x-11 | | -5/4m-1/6=7/3 | | 4x-2=7-2x | | 8+3x-9x=20 | | 0=1-x+y | | 12x+3x-7=4x+31 | | 3x+3*(-3)=3 | | 5x+8+x=170 | | h=3(0)+1 | | 3x+3*3=3 | | -16h^2-49h-3=0 | | h=3(-2)+1 | | 3*(-2)+3y=3 | | h=3(-1)+1 | | .3(3z+7)+18.9=.5(3z-6) | | 5km+3=77km | | y-4=-x-1 | | 8-18=38 | | 8-4x=4-(2x+6) | | 9(2z+4)=-23 | | 3(6x+8)=11x-5 | | -4-3x(-2)= | | ept=qt | | -2(m+7)=-31 | | c=17cm | | 15+5x+6X=180 | | -y=5-4x |